(untitled) (Quinto Sol, 2013)
This paper analizes the debate concerning the inclusion of indians into national society, starting from smallpox epidemics occurred in the 1980s at Buenos Aires city. Such epidemics was caused by the massive coming of native prisoners, as a consequence of the military campaign that had been made in 1879 in the pampas región. Diverse social actors, such as the Church, doctors and members of the army, as well as both the catholic and the liberal press, took part in the debate on contagion and vaccination. Actually, it is a controversy between soul salvation or body care, an extremely important issue for both religious and medical discourse in the late 19th century.